Factors affecting the in vitro production of bovine embryos in a commercial program (Research, Society and Development, 2021)
Variability in the production of bovine blastocysts per session of ultrasound-guided follicularaspiration(OPU) is still an obstacle in commercial production.Thus, the objective of the current work was to verify factors that influence in vitro embryo production (PIVE), using data from a commercial laboratory.Data from 2014 to 2016 were analyzed, referring to 799 OPU sessions of adult bovine females of the breeds: Nelore (n=83), Girolando (n=73), Brangus (n=49), HPB (n=20), and Senepol (n=10).The influence of five variables was analyzed: breed, genetic group, frequency of aspiration, type of semen (sexed/conventional), and seasonality (spring/summer vs. autumn/winter) on the rate of viable oocytes, cleavage, and blastocyst production (bl).The protocols for the in vitroproduction of embryos (IVP) followed the routine established by the partner laboratory of the present study. The statistical analysis of the data was performed using SAS, with the Chi-square test.The Girolando and Nelore breeds had a higher (p=0.0001) number of blastocysts/OPU session, as well as the Bos indicus blood group.Blastocyst production was higher (p=0.0059) with sexed semen compared to conventional semen (6.6 x 5.2 bl/OPU session); a higher frequency of aspirations also increased (p=0.005) the number of bl/OPU session (7.7 x 5.9).We conclude that the in vitro production of bovine embryos is influenced by the analyzed factors and knowledge of these variables could guide the commercial use of OPU-PIVE.